Investigating Factors Influencing Adoption of Land Record Management Information System (LRMIS): A Case of Pakistan - Babur Hayat Malik; Cai Shuqin; Mohammad Shamim Talukder; Butt Mattiullah (European Scientific Journal, ESJ, 2016)
Objective of this article is to investigate the factors affecting adoption of Land Record Management Information System (LRMIS) in Pakistan context. Under financial assistance of World Bank, this Pakistan egovernment initiative is based on government’s long term digital strategic policy that aims to reform and modernize Land Record administration and resources. The model formulated here is based on Unified Theory of Acceptance and Use of Technology (UTAUT) and incorporates constructs such as performance expectancy, effort expectancy, and social influence, facilitating conditions, self-efficacy, trust and behavioral intention. The verifiable results exhibited the positive and significant relations for all 14 hypotheses affirmed using seven constructs. The empirical demonstrations and arguments mentioned in this article can assist Pakistan government to enhance upon and to fully avail the potentiality of LRMIS as an effective and serviceable substance for lucid, not bribable governance and towards modernized digital Land Records not only for one province but throughout the country.